family Parvoviridae - Cotmore, Susan F; Agbandje-McKenna, Mavis; Chiorini, John A; Mukha, Dmitry V; Pintel, David J; Qiu, Jianming; Soderlund-Venermo, Maria; Tattersall, Peter; Tijssen, Peter; Gatherer, Derek; Davison, Andrew J (Archives of virology, 2014)
A set of proposals to rationalize and extend the taxonomy of the family Parvoviridae is currently under review by the International Committee on Taxonomy of Viruses (ICTV). Viruses in this family infect a wide range of hosts, as reflected by the longstanding division into two subfamilies: the Parvovirinae, which contains viruses that infect vertebrate hosts, and the Densovirinae, encompassing viruses that infect arthropod hosts. Using a modified definition for classification into the family that no longer demands isolation as long as the biological context is strong, but does require a near-complete DNA sequence, 134 new viruses and virus variants were identified. The proposals introduce new species and genera into both subfamilies, resolve one misclassified species, and improve taxonomic clarity by employing a series of systematic changes. These include identifying a precise level of sequence similarity required for viruses to belong to the same genus and decreasing the level of sequence similarity required for viruses to belong to the same species. These steps will facilitate recognition of the major phylogenetic branches within genera and eliminate the confusion caused by the near-identity of species and viruses. Changes to taxon nomenclature will establish numbered, non-Latinized binomial names for species, indicating genus affiliation and host range rather than recapitulating virus names. Also, affixes will be included in the names of genera to clarify subfamily affiliation and reduce the ambiguity that results from the vernacular use of “parvovirus” and “densovirus” to denote multiple taxon levels.